2017
DOI: 10.1016/j.euroneuro.2016.09.595
|View full text |Cite
|
Sign up to set email alerts
|

The Schizophrenia Risk Gene Product Mir-137 Alters Presynaptic Plasticity

Abstract: Non-coding variants in the human MIR137 gene locus increase schizophrenia risk at a genomewide significance level. However, the functional consequence of these risk alleles is unknown. Here, we examined induced human neurons harboring the minor alleles of four disease-associated single nucleotide polymorphisms (SNPs) in MIR137, and observed increased MIR137 levels compared to major allele-carrying cells. We found that miR-137 gain-of-function causes downregulation of the presynaptic target genes, Complexin-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 38 publications
(45 reference statements)
7
58
0
Order By: Relevance
“…the relative anatomical or physiological strength of connections from either eye to individual cells in the primary visual cortex) and affects the maturation of dendritic spines (Mellios et al, 2011;Tognini et al, 2011). Thus, these studies showed for the first time a function of (Wright et al, 2016;Siegert et al, 2015;Lett et al, 2013) Idiopathic autism Multiple miRNAs (Wu et al, 2016;Mor et al, 2015;Mundalil Vasu et al, 2014) Fragile-X syndrome miR-9, miR-124 ) let-7b/c, miR-125a, miR-181a, miR-296, miR-342 (Wan et al, 2016 miR-125b, miR-132 (Edbauer et al, 2010) miR-125a (Muddashetty et al, 2011) miR-181d (Wang et al, 2015 Rett syndrome miR379-410 cluster and other miRNAs (Wu et al, 2010) let-7f (Mellios et al, 2014) miR132-212 cluster (Im et al, 2010) 377 miRNAs (e.g. miR-134, miR-383, miR-382, miR-182) (Cheng et al, 2014) miR-199a (Tsujimura et al, 2015) miRNAs in the activity-dependent maturation of neural circuits, a form of developmental synaptic plasticity, in the mammalian brain in vivo.…”
Section: Synapse Developmentmentioning
confidence: 65%
See 2 more Smart Citations
“…the relative anatomical or physiological strength of connections from either eye to individual cells in the primary visual cortex) and affects the maturation of dendritic spines (Mellios et al, 2011;Tognini et al, 2011). Thus, these studies showed for the first time a function of (Wright et al, 2016;Siegert et al, 2015;Lett et al, 2013) Idiopathic autism Multiple miRNAs (Wu et al, 2016;Mor et al, 2015;Mundalil Vasu et al, 2014) Fragile-X syndrome miR-9, miR-124 ) let-7b/c, miR-125a, miR-181a, miR-296, miR-342 (Wan et al, 2016 miR-125b, miR-132 (Edbauer et al, 2010) miR-125a (Muddashetty et al, 2011) miR-181d (Wang et al, 2015 Rett syndrome miR379-410 cluster and other miRNAs (Wu et al, 2010) let-7f (Mellios et al, 2014) miR132-212 cluster (Im et al, 2010) 377 miRNAs (e.g. miR-134, miR-383, miR-382, miR-182) (Cheng et al, 2014) miR-199a (Tsujimura et al, 2015) miRNAs in the activity-dependent maturation of neural circuits, a form of developmental synaptic plasticity, in the mammalian brain in vivo.…”
Section: Synapse Developmentmentioning
confidence: 65%
“…Moreover, it was reported that decreased levels of miR-137 lead to increased expression of hundreds of genes associated with synaptic transmission and synaptogenesis (Strazisar et al, 2015), suggesting excessive synaptic function as a possible result of MIR137 mutation. Accordingly, miR-137 gain of function in multiple cell lines was shown in another study to lead to decreased mRNA translation of numerous mRNAs encoding presynaptic proteins (Siegert et al, 2015), which in turn resulted in impaired presynaptic function due to a decreased number of neurotransmitter vesicles close to the synaptic cleft (Siegert et al, 2015). Intriguingly, miR-137 function is not restricted to the presynapse: miR-137 was also shown to target mRNA encoding the AMPA-type glutamate receptor subunit GluA1 (Olde Loohuis et al, 2015).…”
Section: Synapse Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It interacts with other genes and forms a transcriptional network to regulate differentiation in various cell types. The TCF4 gene has been identified as a target for the microRNA 137 (miR137) gene product, miRNA137, which is asociated with schizophrenia and severe cognitive abnormalities (21). miR137 is involved in neurogenesis and neuronal differentiation.…”
Section: Genementioning
confidence: 99%
“…Moreover, functional MRI (fMRI) studies have demonstrated that variation in miR-137 specifically influences the activity of the posterior right medial frontal gyrus during a cognitive task and functional connectivity of the front-amygdala and dorsolateral prefrontal-hippocampus in emotional tasks [36,37] . Another study has also shown that increased miR-137 expression levels lead to the downregulation of presynaptic target genes such as complexin-1 (Cplx1) and synaptotagmin-1 (Syt1) in vitro and in vivo, causing impairments of synaptic vesicle trafficking and alterations in synaptic plasticity [38] .…”
Section: Mirnas In Neurodevelopmental Disordersmentioning
confidence: 99%